Association of the EPHA1 gene polymorphism with idiopathic mild intellectual disability - Gulkovskyi, R.V.; Livshits, L.A.; Sivolob, A.V. (Вiopolymers and Cell, 2015)
Aim. To investigate a possible association of the EPHA1 gene polymorphism with mild intellectual disability (ID). Methods. The group of patients with mild (IQ score between 50 and 70) idiopathic intellectual disability consisted of 65 individuals including 41 (63.1 %) males and 24 (36.9 %) females. The control group consisted of 250 healthy volunteers from different regions of Ukraine. The genotyping was performed using PCR followed by RFLP analysis for rs11768549, rs11767557, rs11771145 and ARMS PCR analysis for novel c.1891G>A EPHA1 gene mutation. Results. The data concerning the EPHA1 genotypes and allelic variants distribution in ID patients and control group were obtained. Statistical analysis showed a significant association of minor rs11768549-A allele (OR = 3.96, 95 % CI = 1.13 – 13.89) and wild-type rs11767557-T (OR = 1.99, 95 % CI = 1.18 – 3.37) and rs11771145-G (OR = 1.55, 95 % CI = 1.02– 2.37) alleles with a higher risk of mild ID development (p< 0.05 for all). Conclusions. Our results suggest that SNPs (rs11768549, rs11767557, rs11771145) in the EPHA1 gene are associated with idiopathic mild intellectual disability. Therefore, we propose the EPHA1gene as a new candidate gene and the polymorphisms rs11768549, rs11767557, rs11771145 as new markers of genetic susceptibility for intellectual disability. Мета. Дослідити можливу асоціацію поліморфізму гена EPHA1 з легкою інтелектуальною недієздатністю (ІН). Методи. Група пацієнтів з легкою (IQ між 50 і 70) ідіопатичною інтелектуальною недієздатністю складалася з 65 індивідів, включаючи 41 (63.1 %) чоловіків і 24 (36.9 %) жінки. Контрольна група складалася з 250 здорових добровольців з різних регіонів України. Генотипування проводили за допомогою ПЛР з подальшим ПДРФ аналізом для rs11768549, rs11767557, rs11771145 та алель-специфічної ПЛР для нової c.1891G>A мутації в гені EPHA1. Результати. Отримані дані про розподіл генотипів і алельних варіантів гена EPHA1 в групі пацієнтів з ІН і в контрольній групі. За результатами статистичного аналізу встановлено достовірну асоціацію мінорного rs117685 49- A алеля (OR = 3.96, 95 % CI = 1.13 – 13.89) і алелів дикого типу rs11767557-T (OR = 1.99, 95 % CI = 1.18–3.37) та rs11771145-G (OR = 1.55, 95 % CI = 1.02 – 2.37) з більш високим ризиком розвитку легкої ІН (р < 0,05 для всіх). Висновки. Наші результати показують, що SNPs (rs11768549, rs11767557, rs11771145) в гені EPHA1 асоційовані з легкою ідіопатичною інтелектуальною недієздатністю. Тому ми пропонуємо EPHA1 як новий кандидатний ген, а поліморфізми rs11768549, rs11767557, rs11771145 – як нові маркери генетичної схильності до інтелектуальної недієздатності. Цель. Исследовать возможную ассоциацию полиморфизма гена EPHA1 с легкой интеллектуальной недееспособностью (ИН). Методы. Группа пациентов с легкой (IQ между 50 и 70) идиопатической интеллектуальной недееспособностью состояла из 65 индивидов, включая 41 (63.1 %) мужчин и 24 (36.9 %) женщины. Контрольная группа состояла из 250 здоровых добровольцев из разных регионов Украины. Генотипирование проводили посредством ПЦР с последующим ПДРФ анализом для rs11768549, rs11767557, rs11771145 и аллель-специфической ПЦР для новой c.18 91G>A мутации в гене EPHA1. Результаты. Были получены данные о распределении генотипов и аллельных вариантов гена EPHA1 в группе пациентов с ИН и в контрольной группе. Статистический анализ показывает достоверную ассоциацию минорного rs11768549-A аллеля (OR = 3.96, 95 % CI = 1.13 – 13.89) и аллелей дикого типа rs11767557-T (OR = 1.99, 95% CI = 1.18 – 3.37) и rs11771145-G (OR = 1.55, 95 % CI = 1.02– 2.37) с более высоким риском развития легкой ИН (р <0,05 для всех). Выводы. Наши результаты показывают, что SNPs (rs11768549, rs11767557, rs11771145) в гене EPHA1 ассоциированы с легкой идиопатической интеллектуальной недееспособностью. Поэтому мы предлагаем EPHA1 в качестве нового гена кандидата и полиморфизмы rs11768549, rs11767557, rs11771145 в качестве новых маркеров генетической предрасположенности к интеллектуальной недееспособности.